Government Measures to Limit the Impact of Expatriate Labor on Saudi Society (Al-Mostansiriyah journal for Arab and international studies, 2025)
This research aims to examine the reality of expatriate in the kingdom of Saudi Arabia in terms of terms of the reasons for its recruitment and spread across various fields as well sa its political ,economic and social impact.The research also addresses the the risks that may arise from its increasing numbers in Saudi socity both in terms of security andstability and the emergence of undesirable behaviors within society.Economic aspects are among the most prominent impacts as expatriateLabor contributes to rising unemployment rates among Saudi youth as a resoult of preferring to employ them in vital fields at the expense of citizens.Thish hinders economic development efforts within the Kingdom and negatively impacts the states performance. Socially this has resulted in the emergence of patterns of customs and traditions that differ from the conservative Saudi society leading to cultural and behavioral conflict in some cases. Accordingly,the Kingdom of Saudi Arabia has taken a series of governmental and regulatory measures aimed at regulating the number of expatriate workers and reducing the associated risks while working to attract skilled talent who will effectively contribute to the developmentProess in its human, social,and economic aspects.